Komunikasi Efektif Motivator Ketahanan Keluarga Dalam Pemberdayaan Masyarakat - Rini Rinawati; Ferry Darmawan; Dedeh Fardiah; Nia Kurniati (Universitas Garut, 2022)
Abstract Family Resilience Motivator (Motekar) is a Motivator who has the task of assisting the government in building family resilience, especially in West Java. Motekar workers have a very strategic role in realizing family resilience. The role of the motekar power is as an